The Importance of the Evil Forest in Things Fall Apart in the Wake of Climate Change (British Journal of Multidisciplinary and Advanced Studies, 2025)
This paper explores the importance of the Evil Forest in Things Fall Apart and its implications for contemporary environmental conservation, arguing that indigenous knowledge systems can contribute to climate change mitigation and adaptation strategies.